Management of intra-abdominal infections: recommendations by the Italian council for the optimization of antimicrobial use - Massimo Sartelli; Carlo Tascini; Federico Coccolini; Fabiana Dellai; Luca Ansaloni; Massimo Antonelli; Michele Bartoletti; Matteo Bassetti; Federico Boncagni; Massimo Carlini; Anna Maria Cattelan; Arturo Cavaliere; et al. (World Journal of Emergency Surgery, 2024)
Abstract Intra-abdominal infections (IAIs) are common surgical emergencies and are an important cause of morbidity and mortality in hospital settings, particularly if poorly managed. The cornerstones of effective IAIs management include early diagnosis, adequate source control, appropriate antimicrobial therapy, and early physiologic stabilization using intravenous fluids and vasopressor agents in critically ill patients. Adequate empiric antimicrobial therapy in patients with IAIs is of paramount importance because inappropriate antimicrobial therapy is associated with poor outcomes. Optimizing antimicrobial prescriptions improves treatment effectiveness, increases patients’ safety, and minimizes the risk of opportunistic infections (such as Clostridioides difficile) and antimicrobial resistance selection. The growing emergence of multi-drug resistant organisms has caused an impending crisis with alarming implications, especially regarding Gram-negative bacteria. The Multidisciplinary and Intersociety Italian Council for the Optimization of Antimicrobial Use promoted a consensus conference on the antimicrobial management of IAIs, including emergency medicine specialists, radiologists, surgeons, intensivists, infectious disease specialists, clinical pharmacologists, hospital pharmacists, microbiologists and public health specialists. Relevant clinical questions were constructed by the Organizational Committee in order to investigate the topic. The expert panel produced recommendation statements based on the best scientific evidence from PubMed and EMBASE Library and experts’ opinions. The statements were planned and graded according to the Grading of Recommendations Assessment, Development and Evaluation (GRADE) hierarchy of evidence. On November 10, 2023, the experts met in Mestre (Italy) to debate the statements. After the approval of the statements, the expert panel met via email and virtual meetings to prepare and revise the definitive document. This document represents the executive summary of the consensus conference and comprises three sections. The first section focuses on the general principles of diagnosis and treatment of IAIs. The second section provides twenty-three evidence-based recommendations for the antimicrobial therapy of IAIs. The third section presents eight clinical diagnostic-therapeutic pathways for the most common IAIs. The document has been endorsed by the Italian Society of Surgery.